1997
DOI: 10.1111/j.1365-246x.1997.tb01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary ferrimagnetic minerals in Welsh soils: a comparison of mineral magnetic detection methods and implications for mineral formation

Abstract: A range of low-temperature and isothermal magnetic measurements are used to identify the secondary ferrimagnetic mineral (SFM) grain sizes in 10 representative soil samples from Wales. A comparison of percentage frequency-dependent susceptibility ( zFD percentage) and low-temperature remanence measurements shows that they are sensitive to different ranges of superparamagnetic (SP) grains. The relative distributions of SP grains and stable single domain (SSD) grains are similar in nine of the samples. Typical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
119
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(132 citation statements)
references
References 31 publications
8
119
0
5
Order By: Relevance
“…The χ fd % versus χ ARM /SIRM plot (Fig. 5) (Dearing et al, 1997), shows the subway particulate matters are dominated by multi-domain (MD, 10-100 μm for magnetite) and pseudo-single domain (PSD, 1-10 μm for magnetite) particles. The plot also confirms that the magnetic particles in the subway system are finer than the urban particles.…”
Section: Magnetic Mineral Grain Sizementioning
confidence: 98%
“…The χ fd % versus χ ARM /SIRM plot (Fig. 5) (Dearing et al, 1997), shows the subway particulate matters are dominated by multi-domain (MD, 10-100 μm for magnetite) and pseudo-single domain (PSD, 1-10 μm for magnetite) particles. The plot also confirms that the magnetic particles in the subway system are finer than the urban particles.…”
Section: Magnetic Mineral Grain Sizementioning
confidence: 98%
“…Frequency-dependent susceptibility (χfd) can indicate the presence of grains lying at the stable single domain-super-paramagnetic (SSD-SP) boundary, around 0.02 μm for isodiametric grains (Mullins, 1977;Dearing et al, 1996a;Worm, 1998;Dearing, 1999;Lu et al, 2008). Relatively high χfd% indicates the concentration of SP grains in soil, and if it is less than 4%, MD (multi-domain) and PSD (pseudo single domain) or SSD grains dominate (Dearing et al, 1996a(Dearing et al, , 1997Evans and Heller, 2003;Hu et al, 2007). Further, χfd% is correlated with the age and or the degree of soil weathering (Singer et al, 1996;van Dam et al, 2005), and can also be used to estimate the viscous remanent magnetization of the samples.…”
Section: Frequency Dependent Susceptibilitymentioning
confidence: 99%
“…Frequency dependent susceptibility is used to detect ultra-fine (<0.03μm) super-paramagnetic (SP) minerals occurring as crystals produced by bacteria or by chemical processes in the soil (Dearing et al, 1996a(Dearing et al, , 1997Dearing, 1999;Muxworthy, 2001;Maher et al, 2003). In this study, the procedure involved measuring volume magnetic susceptibility at 0.46 kHz (χlf) and 4.6 kHz (χhf).…”
Section: Frequency Dependent Susceptibilitymentioning
confidence: 99%
“…All the samples show χ FD % > 2 but most of the samples fall in between 4-10% suggesting the presence of significant amount of the superparamagnetic magnetite grains. Jordanova [9] has reported that burnt clay samples with χ FD % values of 6-10% contain significant content of fine superparamagnetic magnetite grains of sizes 0.012-0.023 µm [22]. The investigator's results suggest that the pottery samples under investigation are magnetically enhanced materials in terms of concentration and degree of crystallinity of magnetite.…”
Section: Frequency Dependent Susceptibilitymentioning
confidence: 70%